Analysis of Blasting Efficiency Using Crack-Inducing Holes and Pre-Splitting Method in Blasting - Ji-Wan Yoo; Sean Seungwon Lee (Applied Sciences, 2025)
In an era of increased need for underground tunnel excavation to address growing urban population and traffic concerns, complaints resulting from blasting vibrations and the frequent execution of uneconomically inefficient blasting operations due to excessive overbreak have become more prevalent. Therefore, it is necessary to develop blasting methods that can reduce blasting vibrations and minimize overbreak. Various patterns of crack induction holes were placed between the presplitting holes to facilitate the formation of controlled pre-cracks to address the limitations of the presplitting blasting method in this study. The author conducted full-scale experimental blasting at a railway tunnel site and analyzed the blasting effects of the crack induction hole method and pre-splitting technique. As a result of the field test, the pre-formed cracks effectively attenuated vibrations generated in the cut blasting area, reducing blasting-induced vibrations by from 9.3% to 33.5%. Additionally, the amount of overbreak was decreased by from 17.9% to 20.2%. Therefore, the use of crack induction holes and pre-splitting blasting methods in underground tunnel blasting is expected to reduce overbreak, thereby lowering reinforcement costs and minimizing vibrations, preventing damage to adjacent structures. This is expected to enable economically and safely executed tunnel blasting operations both directly and indirectly.